Penerapan Problem Based Learning Berbantuan E-Modul Interaktif untuk Meningkatkan Pemahaman Matematis Volume Bangun Ruang - Maghfirana, Isna Hamida; Jumatin, Jumatin (Jurnal Didaktika Pendidikan Dasar, 2023)
Based on learning observations conducted at Siman 1 Public Elementary School, Ponorogo Regency obtained that the mathematical understanding of grade 5 in determining the volume of geometric volume was not satisfactory. An alternative solution to solve this problem was implementation of Problem Based Learning assisted by interactive e-module. This study aims to describe students’ mathematical understanding on the geometric volume in grade 5. This study used classroom action research from Kemmis & McTaggart. This research has been carried out in three cycles, each cycle was 3x35 minutes long. The result of the study indicated an improve in mathematical understanding, in cycle 1 the percentage of classroom completeness showed 58%, in cycle 2 up to 71%, and in cycle 3 became 79%. Therefore, implementation of Problem Based Learning assisted by interactive e-module could improve students’ mathematical understanding in geometric volume